Factors associated with no apparent coronary artery disease in patients with type 2 diabetes mellitus for more than 10 years of duration: a case control study. Issue 1 (December 2015) - Srinivasan, Mukund; Kamath, Padmanabh; Bhat, Narayan; Pai, Narasimha; Manjrekar, Poornima; Mahabala, Chakrapani
Abstract Background Type 2 diabetes mellitus is an important risk factor in the development of coronary artery disease (CAD) and is often associated with severe disease. However, this risk is not uniform, some patients remain free of CAD even after many years of treatment for diabetes. The present study was aimed to identify the factors that are associated with a favorable CAD profile. Methods A case–control study of 76 patients with type 2 diabetes mellitus who were on treatment for more than 10 years duration and undergoing a coronary angiogram for the evaluation of clinically suspected CAD at a tertiary care hospital were recruited for the study. The presence and absence of significant CAD was determined after a coronary angiogram. Clinical history, and anthropometric and biochemical parameters were analyzed. Insulin resistance was determined by the Homeostasis Model Assessment. Multiple logistic regressions were done to find out the factors associated for a favorable CAD profile. Results The difference in HOMA-IR (2.37 ± 0.69 VS 3.77 ± 1.64, p < 0.001) and urine microalbumin (24.15 ± 32.16 VS 82.72 ± 117.70, p = 0.004) were found to be statistically significant among those who did not have CAD when compared to those who had CAD. The difference in lipid profile, HbA1C, fasting blood sugar, BMI, waist hip ratio, waist and hip circumference was not significant. The adjusted odds ratio for insulin resistance less than 2.5 (OR 9.09, 95 % CI 1.91–41.83, p = 0.005), females (OR 7.91, 95 % CI 1.55–40.38, p = 0.013) and microalbumin <20 mg/l (OR 4.57, 95 % CI 1.17–17.85, p = 0.029) were independently associated with normal coronaries. The adjusted odds ratio for lipid profile, BMI, blood pressure and HbA1C were not significant. Conclusions HOMA-IR less than 2.5, microalbuminuria less than 20 mg/l and females are the factors appear to be associated with no apparent CAD.